Pengaruh Return On Assets, Return On Equity, Debt To Equity Ratio, Inflasi, Dan Suku Bunga Terhadap Return Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Secondary Sectors Periode 2010-2015) - Hikmawati, Ningsih; Wiratno, Adi; Suyanto, Suyanto; Darmansyah, Darmansyah (Institut Bisnis dan Informatika Kesatuan, 2018)
This study is aimed to ascertain and analyse the influence of return on assets, return on equity, debt to equit ratio, inflation, and interest rate, both partiall and simultaneously on the stock returns in manufacturing companies of secondary sectors listed in the Indonesian Stock Exchange. This research uses quantitative methods and EVIEWS panel 8 to analyse the regression. The population are manufacturing companies of secondary sector listed in the Indonesian Stock Exchange consisted of basic and chemical sectors, miscellaneous industry, and consumer goods sector in the period of 2010-2015. The sampling method used is pusposive sampling with the final number of 40 companies. The research required secondary data. The results show that return on assets has no negative effect on stock return, mean while, return on equity and interest rate have positive effect on stock return. Return on assets, return on equity, debt to equity ratio, inflation and interest rate all simultaneously have effect on stock returns.